Exploring three idealised cognitive models in The Kampung Boy and Budak Kampung - Khazriyati Salehuddin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The notion “language mirrors the structure of human cognition” is applicable, especially when the same ideas are presented to different speech communities. This is so because speakers of different speech communities do not see a particular concept in a similar manner. Their experiences are the key factors as to why they express certain concepts in certain ways. This paper compares and contrasts three Idealised Cognitive Models (ICMs) namely, kinaesthetic image schemas, conceptual metaphors, and metonymies, that underlie the linguistic expressions in Dato’ Lat’s graphic novel, The Kampung Boy, with the ICMs found in its Malay version, Budak Kampung. This is to investigate if the thought processes in both languages, especially when conveying the same ideas, are similar or otherwise. Results show that the ICMs that were used in The Kampung Boy were either maintained, modified, dropped, or added in its Malay version. This paper suggests that no individuals experience and perceive the same things similarly despite belonging to the same culture and the same linguistic community. In addition, it also supports the notion that knowledge in the similarities and differences in the conceptualisation of ideas by people across cultures is important as it enables those from different linguistic backgrounds to appreciate the linguistic expressions used by different speech communities. This hence, helps them to understand the cultures of people all over the world without having to directly be in physical contact with them.